Senior citizens losing vision as a challenge to contemporary special education - CZERWIŃSKA, KORNELIA; KUCHARCZYK, IZABELLA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Kornelia Czerwińska, Izabella Kucharczyk, Senior citizens losing vision as a challenge to contemporary special education. Interdisciplinary Contexts of Special Pedagogy, no. 25, Poznań 2019. Pp. 333-351. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2019.25.14 Acquiring blindness or low vision at the senior age usually results in decreased quality of life due to a decrease in functional performance in the areas of activities of everyday activities, spatial orientation and mobility, physical activity, spending free time and obtaining information. Loss of vision also implies serious emotional consequences, which in the absence of professional therapeutic help and social support can lead to mental health disorders. Research analyses indicate that the level of satisfying rehabilitation needs of seniors who are losing vision is relatively low, and the specificity of their functioning resulting from the coexistence of various health problems is rarely included in support programs. The aim of the article is to indicate areas that have been so far neglected in the rehabilitation of elderly people who have acquired visual impairment and to formulate proposals aimed at increasing the availability and quality of therapeutic services for this social group.